Security concerns in eGovernment agent-based interoperability - Marques, Fábio (2009)
The use of Information and Communication Technology in the delivery of public services has a number of advantages. In a first approach, it allows productivity and quality improvements in the delivered services and it allows reductions on the running costs. Furthermore, with interoperability between dispersed IT systems, it is possible to deliver enhanced, combined services. The security on eGovernment Information Systems is pivotal, even more when we are talking about security in interoperability eGovernment architectures. This paper presents a brief description of the functionalities of software agents and their important role for building flexible, agent-based interoperability architectures. Our contribution is the identification of new security issues inherent to agent-based interoperability architectures, some possible solutions to those issues and remaining open questions for future work.